THE IMPLEMENTATION OF THE POPULATION CONTROL SYSTEM IN NORTH MINAHASA REGENCY NORTH SULAWESI PROVINCE - Suraji, Suraji; Kansil, Jouhari; Bura, Arnold Fedinan; Pusung, Piet Hein; Jaftoran, Ferdinand (Registratie, 2024)
This research investigated the implementation of population control systems, the associated challenges, and the strategies employed in North Minahasa Regency. It utilized a qualitative research approach with a case research methodology. Key informants included the Head of the DPPKB Office, the Secretary of the Service, the Head of the Population Control, Advocacy, Mobilization, and Information Division, the Head of the Policy Integration Section, Planning and Population Impact Analysis, the Head of the Advocacy Section, Communication, Information, and Education, Inter-Agency Relations Development and Field Lines, the Head of the Planning and Finance Sub-Division, KB Counsellors, Bappeda Staff, and the Legal Section Staff of the North Minahasa Regency Government. Data were collected through interviews, observations, and documentation studies, with validity ensured by triangulation techniques. Data analysis followed the Miles and Huberman Model, involving data collection, reduction, presentation, and conclusion drawing. The findings showed that the implementation of population control in North Minahasa Regency adhered to the Grand Design of Population Development for 2020-2035, which included programs and activities aimed at managing population quantity, enhancing population quality, and directing population mobility. Challenges identified included limited human resources, inadequate facilities and infrastructure, insufficient budget support, and the absence of Regional Regulations on Population Control. Strategies to address these issues included personnel development, leveraging family planning extension workers, competency enhancement, optimizing budget and facility use, and improving communication, coordination, and partnerships with relevant stakeholders.